Senior Brazilian researchers’ experiences and practices: perceived needs of novice researchers to become part of the community - Leal, Malyina Kazue Ono (Letras, 2022)
Academic writing in English challenges graduate students and novice researchers (FLOWERDEW, 2000; NYGAARD, 2015; HYLAND, 2019). Their lack of experience writing academic genres contrasts with the demand to publish research articles in renowned journals in order to complete their degrees and advance in their careers. Research shows that EAP instruction (WINGATE, 2015), understanding publication as a social practice (CURRY & LILLIS, 2019; NYGAARD, 2015), and English language proficiency (FERGUSON, et al., 2011) are areas where novices need support to successfully engage in the activity. In this study, data was collected from 41 Brazilian researchers regarding their experiences and needs.